Symbolic Compliance vs. Substantive Action: A Comparative Analysis of Sustainability Disclosure Quality Between Major Indonesian and International Banks - Farid Dwiputra; Muchlis Muchlis; Batara Maju Simatupang; Antyo Pracoyo (Jurnal Inovasi Global, 2026)
This study aims to examine and compare the sustainability disclosure quality of major Indonesian banks and leading international banks. Using a quantitative content analysis method, eight banks—four Indonesian and four international—were analyzed through their 2024 Sustainability Reports based on the Global Reporting Initiative (GRI) Standards Consolidated 2021. A dual-tier scoring framework was applied to measure disclosure quality across quantitative, qualitative, and third-party verification dimensions. The findings reveal that although the aggregate disclosure scores appear similar between the two groups, fundamental contrasts exist in strategic focus. Indonesian banks tend to emphasize disclosure quantity and economic aspects, yet exhibit low levels of external assurance. Conversely, international banks demonstrate stronger commitment toward environmental and social disclosures, supported by higher verification credibility. These discrepancies highlight the tension between symbolic compliance and substantive action, reflecting differing regulatory pressures and market expectations. This study contributes empirical evidence to signaling and agency theory in the sustainability reporting context and provides actionable insights for regulators and stakeholders to strengthen accountability and mitigate greenwashing risks.